Experimental study of flexural behaviour of layered steel fibre reinforced concrete beams - Martínez-Pérez, Inmaculada; Valivonis, Juozas; Šalna, Remigijus; Cobo-escamilla, Alfonso (Journal of Civil Engineering and Management, 2017)
The building of structures from steel fibre reinforced concrete (SFRC) in the external and conventional reinforced concrete (RC) in the internal layer represents an economical alternative of structures effectively using SFRC. The paper presents test results of flexural behaviour of layered beams with SFRC external layers and RC internal layer. The behaviour of these beams is compared to test results of SFRC and conventional RC beams. The test results show, that the flexural load capacity for all series of beams is nearly similar, but the deflections of layered beams are less comparing to monolithic ones. It also been shown that the equations indicated in the Eurocode 2 can be used to design the flexural reinforcement in layered SFRC beams.